A case of massive infestation of a male green lizard Lacerta viridis/bilineata by castor bean tick Ixodes ricinus (Linnaeus, 1758) - Veronica Gomes; Anamarija Žagar; Miguel A. Carretero (Natura Sloveniae)
Infestation by ticks affects several vertebrate groups, including reptiles. Castor bean tick Ixodes ricinus is the most widespread tick species. Here we report an impressive tick infestation of a male green lizard Lacerta viridis/bilineata found in 2012 in the vicinity of Bilpa cave in the Kolpa valley, Slovenia. Lizards as tick hosts can play an important role in the life cycle of I. ricinus and may also be potential vectors of Lyme disease.